Comparing the rate of inpatient admissions of prison residents with COVID-19 to the general population in England in 2020/2021 using Hospital Episode Statistics data - Miranda Davies; Anjana Roy (BMJ Public Health)
Objective To compare the rate of inpatient admissions of prison residents with COVID-19 to the general population and to consider differences in the use of inpatient and outpatient services by prison residents in England in the first year of the pandemic (2020/2021), to the 12 months prior to the pandemic (2019/2020).Methods The pseudonymised records of patients who accessed admitted patient care and outpatient hospital services from a prison address in England between 1 April 2019 and the 31 March 2021 were extracted from Hospital Episode Statistics data. Descriptive statistics summarise the most common primary admitting diagnosis and the proportion of outpatient appointments attended and not attended. Indirectly standardised adjusted admission rate was calculated to compare the rate of inpatient admissions by prison residents with COVID-19 to the general population.Results The standardised adjusted admission rate for COVID-19 was 2.2 times higher in prison than the general population. Hospital data highlight continuing challenges regarding high levels of violence and self-harm resulting in hospital admissions during a period when people were spending an increasing amount of time in their cells.Conclusions Despite efforts to minimise the spread of COVID-19 in secure settings, prison residents in England were significantly more likely to be hospitalised with a COVID-19 diagnosis relative to the general population during the first year of the pandemic. This is in addition to the wider implications of the COVID-19 restrictions, particularly spending extended periods in isolation, on people’s mental health.